Painel de sinalização para monitoramento dos pinos de cisalhamento dos geradores da Casa de Força II da UHE Tucuruí - OLIVEIRA, Bruno Gonçalves de (2018)
The project proposal is applied to the speed control system of the generating units of the Tucuruí HPP. The regulation system and consists of go-rivers components, which makes the speed control of the generator, problems in identifying which pin is broken, (a regulatory system component), brings much trouble for HPP maintenance team, bringing the need for the maintainer access location (indoor space) in order to identify which pin is with the abnormality. As the braking system environment is unhealthy, and periculoso antiergonômico, about 2 hours are required for the verification of the problem, it becmes intensely uncomfortable and dangerous to the maintainer. Moreover, the effects extend to the financial losses levels of the company for the delay in resolving the problem. The purpose of this project is to redu-tion risk exposure time by the maintainer and the reduction of the damage that this causes to the institution. Thus, the creation of a device capable of monitoring and reporting, in advance, the maintenance teams, the status and location of a broken shear pin which are in no accor-ness, when it occurs the anomaly is a solution very favorable, because it allows the operator / maintainer check before entering the generator, all the information you need to know to make the intervention. This device will be-efits as comfort, safety and better self-esteem to the employee as well as increased revenue to the company by decreasing the UGH downtime for the system. Currently it is implemented replication of improvement for the other units of the installation. New enhancements to this project are being studied, for example, sending this information to the supervisory system in the plant control room allowing operation in real time, immediately identify the situation and already inform the maintenance team.